Prioritizing restoration and fire preparedness at the public-private boundary - Cyphers, Laren Alise, author; Mackes, Kurt, advisor; Schultz, Courtney, advisor; Jones, Kelly, committee member (Colorado State University. Libraries, 2018)
System processes, like wildfire, will continue to threaten life and property, particularly if land managers cannot work across the public-private boundary at large enough scales. Addressing the wildfire challenge will require more natural fire use and other fuel reduction strategies, like mechanical thinning and prescribed fire, to reduce hazardous fuels. As the wildland-urban interface continues to expand, so does the need to work across the public-private boundary and engage private landowners to create defensible space and address fuel loads where the goal is to reduce fire hazard. This two-part thesis informs the prioritization of funding and management activities related to wildfire management across the public-private boundary. Chapter One of this study reviews three Colorado wildfires, identifying the true costs of the fires through document review and conversations with government and community personnel. This cost data demonstrates the long-term unsustainability of current wildfire management and informs prioritization of funding and management based on an area's forest and land-use type. Chapter Two evaluates the effectiveness of the Joint Chiefs Partnership in tackling the challenge of large-scale, collaborative, cross-boundary work, based on the adaptive governance literature and my qualitative research on the Partnership to understand which aspects of the design of the authority supported that goal. Our research investigated the complete cost of wildfire and the effectiveness of the Joint Chiefs Partnership to inform prioritization of funding for restoration and fire preparedness and understand how policy can be better designed to support such work, particularly across agencies and jurisdictions.